The Development of the PaperBots Robotics Kit for Inexpensive Robotics Education Activities for Elementary Students. - O'Connell, Brian. (2017)
Abstract: In this thesis, I describe an electronics kit that enables robotic education activities that make use of readily available classroom materials. The developed product, PaperBots Robotics Kit, opens up accessibility to robotics education for users who formerly could not afford many of the available options. The design considers cost for the intended stakeholders, teachers, and usability for the end users, students, as well as test group feedback and production. This tool kit enables students to build their robot utilizing paper, cardstock, craft sticks, tape, straw and other craft materials common to a classroom. The controller is an Arduino based development board that is programmable by either the Arduino environment or with LabVIEW. Test groups of kindergarten to six grade students successfully constructed robots using paper, craft materials, and the PaperBots Robotics Kit. They were able to intuitively construct with the materials and the kit and program their robots using a provided LabVIEW interface. The participants also enjoyed their experiences with the product while gaining some experience in engineering principles. The first two design iterations of the PaperBots Robotics Kit and their subsequent testing are described in this report along with suggestions for further development of the product.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Mechanical Engineering.; Advisor: Brian O'Connell.; Committee: Chris Rogers, Daniel Hannon, and Ethan Danahy.; Keywords: Educational technology, Robotics, and Mechanical engineering.